Evaluation of sulfamethazine removal kinetics using fixed structured bed bioreactor - Romeiro, Guilherme Flandoli; Oliveira, Cristiane Arruda; Tomita, Inês N.; Santos-Neto, Álvaro J.; Zaiat, Marcelo; Lima Gomes, Paulo Clairmont F. (Taylor & Francis, 2017)
The use of anaerobic biomass attached to a support has been recently presented as a good prospect in the treatment of wastewater containing recalcitrant compounds, such as sulfamethazine (SMZ). SMZ has been found in swine wastewater and sewage treatment plants, which motivates assessing their degradation by new wastewater treatment technologies. Thus, this paper describes the use of a continuous fixed structured bed bioreactor for the purpose of evaluating SMZ removal kinetics present in lab-made wastewater. The analysis of SMZ used online solid-phase extraction coupled to liquid chromatography/tandem mass spectrometry (SPE online-LC-MS/MS). Chemical oxygen demand (COD) was also monitored to evaluate the organic matter removal. The bioreactor was operated under mesophilic conditions (30(Formula presented.)C), with a hydraulic retention time of 24 h. In order to evaluate SMZ removal, four different concentration levels were studied: 200, 400, 600, and 800 ng L−1. COD removal efficiency obtained for filtered effluent kept at 91.01% and there was no interference due to the increase of SMZ concentration. For SMZ, the removal efficiencies were of (Formula presented.) for 200 ng L−1 concentration level; (Formula presented.) for 400 ng L−1; (Formula presented.) for 600 ng L−1, and (Formula presented.) for 800 ng L−1. COD removal kinetics presented a first-order apparent removal rate constant ((Formula presented.)) of (Formula presented.) h−1. SMZ also showed a first-order apparent removal rate constant of (Formula presented.) h−1 for the following concentrations levels: 200, 400, 600, and 800 ng L−1.
Keywords: Bioreactor; LC-MS/MS; removal kinetic; sulfamethazine; wastewater